Beneath the surface: On the significance of the underground and underwater landscapes in selected documentaries by Werner Herzog - Kempna-Pieniążek, Magdalena (Polskie Studia Krajobrazowe, 2020)
Werner Herzog’s films grow out of landscapes. The frames opening his works very often present landscapes whose role goes beyond illustrative or informative functions. Analyzing films such as Encounters at the End of the World, Cave of Forgotten Dreams, and Into the Inferno, the text reconstructs the meanings inscribed in Herzog’s underground and underwater landscapes. The journey beneath the surface of spaces dominated by nature usually constitutes an equivalent of the journey into culture in the director’s works. In a sense, they are films laced with reflection about experiencing landscapes. What is more, Herzog undertakes his reflections in the realm of documentary cinema, which is firmly entangled with the category of truth. Entering a landscape is therefore a way of reaching truth for the director—however, not objective but “poetic” and “ecstatic” truth, which, according to the creator, has a much more significant quality than mundane facts.